PESAN VISUAL NASIONALIS PADA KOREO GARUDA TERHADAP SUPORTER INDONESIA (STUDI KASUS INDONESIA VS BAHRAIN 2025) - Rafly Ramadhansyah; RR Roosita Cindrakasih; Sultan Himawan (An Nafi': Multidisciplinary Science, 2025)
This study examines the construction of nationalist visual messages in the “Garuda” choreography (koreo) performed by the Ultras group “La Grande Indonesia” during the 2025 Indonesia vs. Bahrain national football match at Gelora Bung Karno Main Stadium. A qualitative approach with a phenomenological method was employed to explore the subjective experiences of supporters regarding the visual messages presented. Data were collected through in-depth interviews, participatory observation, and documentation. Data analysis used triangulation of sources, methods, and theories to ensure the validity of findings. The results show that nationalist visual messages in the Garuda choreography are constructed through a combination of visual elements such as the Garuda symbol, the red-and-white national colors, slogan typography, and background visuals representing pride and unity. Supporters interpret this choreography as an expression of patriotism, a boost for the team’s spirit, and a collective identity that distinguishes them from other nations’ supporters. The choreography also creates cognitive consonance, where national symbols align with the beliefs and emotions of supporters, thereby reinforcing unity and nationalism. This study concludes that supporter choreography is not merely an aesthetic performance but an effective visual communication medium for instilling national values in public spaces. The findings are expected to contribute to the development of visual communication studies and creative practices in building a nationalist atmosphere through sports.